Identification of Liver and Plasma microRNAs in Chronic Hepatitis B Virus infection - Loukachov, Vladimir V.; van Dort, Karel A.; Maurer, Irma; Takkenberg, R. Bart; de Niet, Anniki; Reesink, Henk W.; Willemse, Sophie B.; Kootstra, Neeltje A. (Frontiers in Cellular and Infection Microbiology, 2022)
Background and Aims With current standard of care a functional cure for Chronic Hepatitis B (CHB) is only achieved in 1-3% of patients and therefore novel therapies are needed. Disease activity during CHB can be determined by a broad range of virological biomarkers, however these biomarkers are also targets for novel treatment strategies. The aim of this study was to identify novel miRNAs that are differentially expressed in plasma and liver in CHB, and determine whether these miRNAs may serve as biomarkers of disease stage or treatment outcome. Methods miRNA Next-Generation-Sequencing of plasma and liver samples from CHB patient and controls was performed to identify differentially expressed miRNAs. The identified candidate miRNAs were validated by qPCR in additional plasma and liver samples from two CHB cohorts. Results Several miRNAs in plasma and liver were found to be differentially expressed between CHB patients and controls. Of the identified miRNAs expression levels of miR-122-5p in plasma were associated with plasma HBsAg, and plasma and liver HBV-DNA levels. Expression levels of miR-223-3p, miR-144-5p and miR-133a-3p in liver were associated with plasma alanine aminotransferase levels. No correlation was observed between miRNA expression levels at baseline and treatment outcome. Conclusions Limited overlap between plasma and liver miRNAs was found, indicating that plasma miRNAs could be useful as biomarkers for treatment outcome or viral activity during treatment. Whereas liver miRNAs are more likely to be regulated by HBV and could be potential therapeutic targets to control viral activity in liver.